2022
DOI: 10.12688/wellcomeopenres.17601.3
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dimorphism in Chronic Hepatitis B Virus (HBV) Infection: Evidence to Inform Elimination Efforts

Abstract: Sexual dimorphism in infectious diseases refers to the different infection susceptibilities and outcomes between males and females, and has been described for many pathogens, including hepatitis B virus (HBV). HBV is a substantial global health problem, with close to 300 million people chronically infected, and accounting for a million deaths each year, with an urgent need for enhanced interventions to support progress towards elimination goals. Sexual dimorphism has a strong influence in HBV infection, with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 142 publications
1
3
2
Order By: Relevance
“…In the said study with PWH being older was only a predictor in univariate analysis similar to the current study [4]. Predictors of HBsAg vary across studies which might be due to lifestyle practices, genotypes as well as host genetics [10,48].…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…In the said study with PWH being older was only a predictor in univariate analysis similar to the current study [4]. Predictors of HBsAg vary across studies which might be due to lifestyle practices, genotypes as well as host genetics [10,48].…”
Section: Discussionsupporting
confidence: 62%
“…The South African study also did not show relationship status as well as the number of lifetime partners as predictors of HBsAg positivity similar to the current study [10]. Most studies reported more HBV in males ,however, for the current study, sex was not a predictor of HBsAg positivity [4,45,47,48]. In a study in PWH in the same communities, the male sex and northern geographic region were independent predictors of HBsAg positivity unlike in the current study.…”
Section: Discussioncontrasting
confidence: 58%
“…Differences in disease susceptibility between men and women have been reported in other diseases as well and might be attributed to differences in behavior and biology. For example, women have been shown to possess a stronger immune response against HBV ( Brown et al, 2022 ) and renal cancer patients ( Ning et al, 2023 ). In the current study, there was no difference in CD4+ T-cell counts or HIV viral load between OBI + and OBI − participants at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…The physical, psychological and social impacts of hepatitis B are strongly influenced by sex and gender: men have higher rates of infection, progression to chronic infection, and complications, related to biological and social factors [ 35 ]. However, women are frequently diagnosed through antenatal screening, which provides access to treatment but presents psychosocial challenges such as health risks to unborn children and exposure to stigma and discrimination due to presumed immorality [ 25 , 27 , 35 ].…”
Section: Intersectionality and Hepatitis Bmentioning
confidence: 99%